Distribution of Third-Stage Length and Risk Factors for Its Prolongation - Shinar, Shiri; Shenhav, Michael; Maslovitz, Sharon; Many, Ariel (American Journal of Perinatology, 2016)
Introduction The aim of our study was to demonstrate the distribution of an uncomplicated third stage and to determine the optimal time for manual intervention. Risk factors for a prolonged third stage were studied.Materials and Methods Computerized data of all vaginal deliveries at our L&D unit from 2010 to 2014 were obtained. Cases of complete and spontaneous placental separation were extracted for further analysis. Cases necessitating manual removal of the placenta due to immediate postpartum hemorrhage (PPH) were also excluded. Patient demographics, obstetrical history, course of delivery, and delivery outcome were assessed, and risk factors for a prolonged third stage were analyzed.Results There were 31,226 vaginal deliveries during the study period. Of these, 25,160 deliveries met inclusion criteria. The median third-stage length was 12 minutes. Within 30 minutes 97% of the placentas separated spontaneously. Independent risk factors for a third stage > 30 minutes included older maternal age, primiparity, history of abortions, twin gestation, and intrapartum fever.Conclusion The average time for third stage is < 15 minutes with 97% occurring by 30 minutes and 100% by 60 minutes. In the absence of PPH, it is clinically prudent to perform manual removal after 30 minutes.
Keywords: third; stage; length; placenta; separation